DIFFERENCE BETWEEN MEANINGS IN UZBEK AND ENGLISH LANGUAGES - Kholmuminova , Makhliyo (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Anthropocentric paradigm of modern linguistic science encourages researchers to solve new problems related to the description of mental units concepts. Moreover, the artistic concept, representing a key unit of the cognitive paradigm of researching an artistic text, had several distinctive features: associative nature, imagery and symbolism, emotiveness, orientation to aesthetic information, dialogically, the variability of semantic content, ability to enrich the meaning, etc. Study of the artistic concept further promoted comprehension of the ideological content of the artistic text, comprehension of the author’s conceptual sphere, and identiﬁcation of the author’s speciﬁc style. The concept is realized in the minds of the humans, and they are associated with tokens.